O18-2 Extracellular vesicles are associated with particulate matter exposure. (1st September 2016) - Pesatori, Angela Cecilia; Carugno, Michele; Pergoli, Laura; Cantone, Laura; Iodice, Simona; Angelici, Laura; Favero, Chiara; Fustinoni, Silvia; Buono, Luca Del; Cattaneo, Andrea; Bonzini, Matteo
Abstract : Background: Exposure to Particulate Matter (PM) has been associated with increased risk for cardiovascular diseases. In the lungs PM triggers the release of extracellular vesicles (EVs) that travel through the bloodstream and reach target organs. EVs might represent an essential component of the effect of PM on human health. Aim: to characterise plasma EVs and assess their association with exposure to PM with diameter ≤10 µm (PM10) and ≤2.5 µm (PM2.5), considering the role of Body Mass Index (BMI). Methods: we recruited 20 male and 30 female healthy volunteers (Nov 2014–Mar 2015) in Milan, Italy, which provided personal information and a blood sample. After centrifugation, EV membrane determinants were characterised by Flow Cytometry (to assess cellular origin from platelets, monocytes, epithelium, endothelium, neutrophils), EV size and counted by Nanosight. Each subject wore a personal air sampler for 24 h, retrieving individual daily mean PM10 and PM2.5 concentrations. Same-day PM10 and PM2.5 data from air quality monitoring stations were also obtained. Associations between PM and log-EV were assessed applying multivariate linear models adjusted for age, sex, BMI and smoking. Results: Personal sampler and monitor data showed a Spearman's ρ of 0.59 (p < 0.001) for PM10 and of 0.68 (p < 0.001) for PM2.5. Regression analysis showed a variation of 10.5% (95% Confidence Interval [CI]: 1.8; 19.8, p = 0.018) in endothelium-derived EV count (CD105+) per 10 µg/m 3 increase in PM10, and of 11.4% (95% CI: 2.0; 21.6, p = 0.017) per an equal increase in PM2.5. When stratifying by BMI, all EV types showed a positive increase in overweight subjects only (BMI ≥ 25) and a null-negative variation in normal weight subjects. Variation in EV-CD105+ was 13.4% (95% CI: 3.3; 24.4, p = 0.011) for PM10 and 14.0% (95% CI: 2.6; 26.7, p = 0.018) for PM2.5 in overweight. Conclusions: Our findings suggest an association between PM exposure and EV, particularly in hypersusceptible subjects.